The banking and credit system of the USSR - Kuschpèta, O. (Leiden ; Boston : Nijhoff Social Sciences Division, 1978)
This book is a study and evaluation of the monetary and banking systems of the USSR from the stand-point of the needs of the Soviet economy itself
"Translated [from the Russian] by: A. H. N. Ryan."
"Distributors for North America Kluwer Boston ... Hingham, Ma."
Includes index.
Bibliography: p. [257]-273.
oo 24/01/2019
Loans
Keywords: Finance; Banks and banking; Credit